Metropolisation through Regionalisation? Spatial Scope and Anchor Points of Metropolitan Functions in German Urban Regions - Anna Growe; Kati Volgmann (Tijdschrift voor economische en sociale geografie, 2022)
Based on topics of research examining how metropolisation processes affect the areas surrounding metropolitan centres and change the locations of metropolitan functions in urban regions, this article examines: (i) how pronounced the process of the regionalisation of metropolitan functions is; (ii) in which sub-areas of a surrounding region the regionalisation of metropolitan functions can be observed and (iii) which places are anchor points of metropolitan regionalisation. The regionalisation processes are studied using a municipal-level dataset of metropolitan functions from German urban regions. The findings indicate that centrifugal forces distribute metropolitan functions across the surrounding region around one or more metropolitan core cities, and that this is, for the most part, linked to medium-sized cities and to the complementary areas of metropolitan centres.
Keywords: 330; metropolisation; metropolitan functions; regionalisation; urban regions; polycentric regions; Germany; surrounding area